Sailing too close to the wind in 1880s Wellington - Humphris, Adrian; Mew, Geoff (Architectural History Aotearoa, 2021)
The 1880s and early 1890s have been widely recognised as a time of depression in New Zealand. While well-known architects with substantial clienteles were generally able to survive the downturn in business, others struggled to make ends meet, showed signs of extreme stress, or occasionally resorted to sharp practices. Few in-depth studies have been able to show the broad spectrum of architects working in Wellington at a particular time as, until recently, it has been extremely difficult to accumulate the necessary data. The introduction of Papers Past has considerably simplified this task. We can now find and assess almost all the architects who made the news in different ways. Although more than 30 men claimed to be Wellington architects in the 1880s, not all of them were working. Some, such as Frank Mitchell, produced relatively large numbers of plans throughout the decade; many others appear to have been less successful, and to have turned their hands to other activities, for better or worse. In this paper we select a few of the more colourful "architects" residing in Wellington in the 1880s. Our candidates range from the aforementioned Frank Mitchell, through to Christopher Walter Worger, who being bankrupted in Christchurch, moved to Wellington in 1889. Leaving no record of any building designs, he had gone to Dunedin by 1906. Another enigmatic character was James Henry Schwabe, who escaped Dunedin and a rather public humiliation for Wellington in the late 1870s. Similarly, we discuss the erratic behaviour of W.J.W. Robinson, also escaping scandal in Dunedin to practise in the capital. Charles Zahl we find making a fleeting visit in early 1887, before absconding with a large sum of investors’ money en route to Rio de Janeiro or Britain. We finish with the case of Ernest Wagner, released into the community after a year’s hard labour in 1880. He never practised as an architect again - preferring, or being forced, to live as a farmer in the country south of Auckland. The examples we discuss are the exception rather than the rule. Of the bankruptcies recorded at the time, few came from the upper echelons of society. Some architects who were later prominent in Wellington moved offshore to better conditions in Australia (such as Joshua Charlesworth), whereas others such as William Turnbull were protected to some extent in successful partnerships in which they had a junior role.